Collaboration Network of Thailand’s Anti-Corruption Organizations - Yomnak, Torplus; Ruckchart, Supparerk (SOUTHEAST ASIAN JOURNAL OF ECONOMICS, 2021)
An efficient collaboration amongst anti-corruption organizations is an important factor for an effective fight against corruption. This research aimed to analyze the network of Thailand’s anti-corruption organizations and compare the property of each collaboration group in the network. Data was collected by interviewing executives of 27 anti-corruption organizations in Thailand from across sectors. The collaboration level between each two organizations rated by interviewees was analyzed and categorized using Social Network Analysis and each collaborative group was categorized by the objective of each organization in that group. The result showed that the network is decentralized which weakens collaborations amongst organizations in the network and thus hinders their work effectiveness. From the data analysis, the research then offers recommendations to improve and enhance the efficiency and sustainability of collaboration in this network.